PENINGKATAN KEMAMPUAN MENULIS TEKS LAPORAN HASIL OBSERVASI DENGAN MENGGUNAKAN PENDEKATAN DISCOVERY DI KELAS X SMA XIX KARTIKA 1 BANDUNG - Rochmat Tri Sudrajat; Dida Firmansyah (STKIP Siliwangi, 2020)
This research was motivated by the lack of students' ability to know, understand and write the text of the observation report as measured by the results of the evaluation and previous interviews with students randomly. Besides, due to the inaccurate use of models, methods, approaches or strategies that are commonly used by teachers in the learning process, it raises problems in planning, implementation and the resulting products. Based on the analysis and observations, the researcher formulated a problem in how the form of planning, implementation and evaluation results from learning to write observation texts using the discovery approach. From the research formulation, the researcher has a specific research objective, namely to determine the planning, implementation and learning outcomes of writing a text report on the observation results using the discovery approach. To achieve this goal, the research method used is Classroom Action Research (CAR) based on previous studies that have succeeded in improving learning outcomes. The subjects of the study were students of class X SMA XIX Kartika 1 Bandung in the 2018-2019 academic year. Based on the results of the description and analysis of data discussion in cycle 1 and cycle II, the ability of students in the Observation Result Report (LHO) material increased by 35%. It can be concluded that the students' abilities have increased through the discovery approach in understanding and writing texts both in terms of text structure and language.